Transverse myelitis caused by schistosomiasis during pregnancy. A case report - Truter, P J; van der Merwe, J V (South African medical journal, 1987)
A rare case of transverse myelitis caused by schistosomiasis of the spinal cord during pregnancy is presented. The diagnosis and treatment are discussed.A rare case of transverse myelitis caused by schistosomiasis of the spinal cord during pregnancy is presented. The diagnosis and treatment are discussed.